1T MoS2atCNTs / Ni3S2 nano composite electrocatalyst and preparation method thereof
By in situ growing carbon nanotubes on a nickel foam substrate and constructing a 1T MoS2@CNTs/Ni3S2 nanocomposite electrocatalyst, the problems of easy deactivation of precious metal catalysts in alkaline environments and loose contact of carbon nanotubes were solved, thereby achieving an improvement in efficient electrocatalytic performance.
Patent Information
- Application Number
- CN202510782417.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-12
- Publication Date
- 2025-09-12
AI Technical Summary
Existing precious metal catalysts are easily dissolved, agglomerated or oxidatively inactivated when used in the oxygen evolution reaction of water electrolysis to produce hydrogen in an alkaline environment. In addition, the carbon nanotubes are not in close contact with the active components, resulting in low charge transfer efficiency, hindering electrolyte penetration and bubble release.
A two-step solvothermal method was used to in situ grow a vertically aligned carbon nanotube transition layer on a nickel foam substrate to form a 1T MoS2@CNTs/Ni3S2 nanocomposite electrocatalyst, construct a core-shell structure and heterojunction, improve the dispersibility and electron transfer efficiency, and form a three-dimensional ordered array.
It significantly improves the electrocatalytic performance, reduces contact resistance, exposes more active sites, promotes electrolyte penetration and rapid bubble desorption, and is suitable for high-efficiency electrocatalytic applications.
Smart Images

Figure CN120625103A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst suitable for electrocatalytic applications, and its application in highly efficient catalytic hydrogen and oxygen evolution reactions in alkaline environments. Specifically, a two-step solvothermal method is used to vertically grow a carbon nanotube (CNT) transition layer on a nickel foam (NF) substrate, followed by the preparation of a novel 1T MoS2@CNTs / Ni3S2 three-dimensional array electrocatalyst. Background Art
[0002] Hydrogen (H2) is considered the most promising future energy carrier due to its ultra-high energy density (120-140 MJ / kg, three times that of gasoline), its combustion product being only water (zero carbon emissions), and its recyclability. However, currently, more than 95% of the world's hydrogen is still produced through fossil fuel reforming (such as methane steam reforming). This method not only relies on non-renewable resources but also produces large amounts of CO2 emissions. Therefore, the development of green hydrogen production technologies, especially water electrolysis driven by renewable energy (such as solar and wind energy), has become a key path to solving energy and environmental problems. Water electrolysis hydrogen production technology has become a research hotspot due to its high-purity hydrogen products and zero carbon emissions. It mainly consists of two half-reactions: the hydrogen evolution reaction (HER, cathode) and the oxygen evolution reaction (OER, anode). However, OER involves a complex four-electron-proton coupled transfer process, resulting in slow kinetics and requiring high overpotentials. Currently, commercial electrolyzers rely on precious metal catalysts (such as Pt / C for HER and IrO2 / RuO2 for OER), but their scarcity and high price severely hinder their large-scale application. Precious metal catalysts are prone to dissolution, aggregation, or oxidative deactivation in strongly alkaline or acidic electrolytes. As an alternative to precious metal electrocatalysts, transition metal sulfides have attracted considerable attention due to their unique electronic structures and low cost.
[0003] The metallic 1T phase of MoS2 has a hydrogen adsorption free energy close to that of Pt, but suffers from a shortage of active sites and poor OER activity. Ni3S2 exhibits superior OER activity compared to NiO / Ni(OH)2, but exhibits weaker HER performance. Constructing a 1T MoS2 / Ni3S2 heterojunction can synergistically optimize HER / OER activity, but interfacial charge transfer efficiency remains insufficient in alkaline environments, and active site exposure is low. Carbon nanotubes (CNTs) are widely used to enhance electrocatalyst performance due to their ultrahigh conductivity, π-electron delocalization, and mechanical stability. The one-dimensional hollow structure of CNTs provides fast electron transfer channels and reduces interfacial resistance. Their surface π-electron cloud optimizes charge distribution at metal sites and modulates the adsorption strength of intermediates (such as H and OOH). The flexible CNT network buffers electrolyte impact and prevents active species from shedding. However, randomly interwoven CNTs block pores, hindering electrolyte penetration and bubble release. Physically mixed CNTs tend to form non-intact contacts with active species, resulting in reduced charge transfer efficiency. Summary of the Invention
[0004] To address the above problems, the present invention proposes a 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst and a preparation method thereof. The 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst is an in-situ grown vertically arranged large inner diameter thin-walled carbon nanotube (CNTs) transition layer on nickel foam (NF). A typical core-shell structure is formed with carbon nanotubes as cores and 1T MoS2 as shells on top of the carbon nanotubes. NF is used as a Ni source, and Ni3S2 is generated after sulfurization. It forms a heterojunction with the 1T MoS2@CNTs core-shell structure on the surface, forming a 1T MoS2@CNTs / Ni3S2 three-dimensional ordered array.
[0005] The preparation method of the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst comprises the following specific steps: (1) In situ growth of CNTs on nickel foam: Dissolve 6.0-6.5 mmol of citric acid monohydrate (C6H8O7·H2O) in 14-16 mL of a 1:1 volume ratio of anhydrous ethanol and deionized water. After stirring for 10 minutes, add 0.4-0.5 g of urea and 0.1-1.0 mmol of large-diameter, thin-walled carbon nanotubes (CNTs). After sonication for 30 minutes, transfer the solution to a reactor (filling the reactor with no more than 80% of its capacity). Add nickel foam (NF) and react at 170-185°C for 12-18 hours. After cooling the reactor, rinse the sample with ethanol and deionized water and dry it to obtain NF with CNTs grown on it. (2) Preparation of CNTs-supported 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst: Then, 1.5 mmol of thioacetamide (CH3CSNH2) and 0.5 mmol of sodium molybdate dihydrate (Na2MoO4·2H2O) were dissolved in 14-16 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1 and stirred evenly. The NF with grown CNTs was placed in a reactor. The solution filling amount should not exceed 80% of the reactor capacity. The above solution was added and reacted at 115-125°C for 6-12 hours and then at 190-210°C for 8-14 hours. After the reactor was cooled, the obtained sample was washed and dried to obtain the CNTs-loaded 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst.
[0006] Preferably, the nickel foam (NF) in step (1) is pretreated by the following steps: The samples were washed with 3.0 M HCl for 10 min, then washed with acetone and deionized water several times to remove surface impurities, and dried in a vacuum at 60 °C for 6 h.
[0007] Preferably, the mixed solution in step (1) and step (2) is prepared by mixing 7.5 mL of anhydrous ethanol and 7.5 mL of deionized water.
[0008] Preferably, the reaction is carried out at 180°C for 12 h in step (1), and the reaction is carried out at 120°C for 6 h and then at 200°C for 8 h in step (2).
[0009] Preferably, in step (1), 0.7 mmol of large inner diameter thin-walled carbon nanotubes (CNTs) are added.
[0010] Beneficial effects of the present invention: 1. This invention adopts a simple two-step solvothermal method to load CNTs on NF, which does not require complex equipment and significantly reduces production costs, thereby preparing a highly efficient nanocomposite electrocatalyst suitable for electrocatalytic applications.
[0011] 2. This method, based on nickel foam, utilizes CNTs to bridge 1T-MoS2 and Ni3S2, significantly improving the dispersion of 1TMoS2, facilitating electron transfer, reducing contact resistance, and exposing more effective active sites. The three-dimensional open structure promotes electrolyte penetration, enhances mass transfer efficiency, ensures rapid bubble desorption at high current densities, and enhances electrocatalytic performance.
[0012] 3. The present invention uses large inner diameter, thin-walled multi-walled carbon nanotubes. Their large inner diameter can provide more electron transmission channels, increase the loading capacity of 1T MoS2, and thus facilitate the construction of a three-dimensional ordered array. Their thin walls are conducive to reducing contact resistance and improving electrochemical reaction kinetics.
[0013] 4. The present invention is not only simple to operate and has clear steps, but also has the advantages of being green, environmentally friendly, economical, convenient, and highly reproducible, and is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is the X-ray diffraction pattern of 1T MoS2 / Ni3S2 and 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalysts; Figure 2 This is the scanning image and elemental mapping of 1T MoS2 / Ni3S2 nanocomposite electrocatalyst; Figure 3 The scanning image, EDS spectrum and elemental mapping of 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst; Figure 4 TEM and HRTEM images of 1T MoS2@CNTs / Ni3S2; Figure 5 The results of hydrogen evolution properties test of 1T MoS2 / Ni3S2 and 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalysts are shown; Figure 6 The oxygen evolution properties test results of 1T MoS2 / Ni3S2 and 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalysts; Figure 7 This is the test result of the full water splitting performance of 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst. DETAILED DESCRIPTION
[0015] The technical solution of the present invention is further explained and illustrated in the following in the form of specific embodiments.
[0016] The raw materials required in the embodiments of the present invention are as follows: Large inner diameter thin-walled carbon nanotubes (CNTs, Aladdin reagent) were of analytical grade; Urea (H2NCONH2, Aladdin reagent) was analytical grade; Citric acid monohydrate (C6H8O7·H2O, Sinopharm Chemical Reagent Co., Ltd.) was of analytical grade; Sodium molybdate dihydrate (Na2MoO4·2H2O, Aladdin reagent) was of analytical grade; Thioacetamide (CH3CSNH2, Sinopharm Chemical Reagent Co., Ltd.) was of analytical grade; Hydrochloric acid (HCl, Sinopharm Chemical Reagent Co., Ltd.) was of analytical grade; Acetone (CH3COCH3, Sinopharm Chemical Reagent Co., Ltd.) was of analytical grade.
[0017] Example 1 (Preparation of 0.7% CNTs-loaded 1T MoS2@CNTs / Ni3S2 Nanocomposite Electrocatalyst) (1) Pretreatment of nickel foam: NF (20 mm × 30 mm) was washed with 3.0 M HCl for 10 min, then washed several times with acetone and deionized water to remove surface impurities, and dried under vacuum at 60 °C for 6 h.
[0018] (2) In situ growth of CNTs on nickel foam: 1.337 g of citric acid monohydrate (C6H8O7·H2O) was dissolved in a mixture of 7.5 mL of anhydrous ethanol and 7.5 mL of deionized water. After stirring for 10 min, 0.45 g of urea and 0.7 mmol of large inner diameter thin-walled carbon nanotubes (CNTs) were added. After ultrasonication for 30 min, the solution was transferred to a 20 mL reactor and NF was placed in it. The reaction was continued at 180 °C for 12 h. After the reactor was cooled, the sample was repeatedly rinsed with ethanol and deionized water and dried at 60 °C for 6 h to obtain NF with CNTs grown on it. (3) Preparation of CNTs-supported 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst: Then, 1.5 mmol of thioacetamide (CH3CSNH2) and 0.5 mmol of sodium molybdate dihydrate (Na2MoO4·2H2O) were dissolved in a mixed solution of 7.5 mL of anhydrous ethanol and 7.5 mL of deionized water and stirred for 30 minutes. The NF with CNTs grown on it was placed in a 20 mL reactor and the above solution was added. The reaction was first carried out at 120°C for 6 hours and then at 200°C for 8 hours. After the reactor was cooled, the obtained sample was repeatedly rinsed with ethanol and deionized water, and finally dried at 60°C for 6 hours to obtain the CNTs-supported 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst.
[0019] Comparative Example (1T MoS2 / Ni3S2 Nanocomposite Electrocatalyst) Dissolve 1.5 mmol of CH₃CSNH₂ and 0.5 mmol of Na₂MoO₄·2H₂O in a mixture of 7.5 mL of anhydrous ethanol and 7.5 mL of deionized water and stir for 30 minutes. Place the NF in a 20 mL reactor and add the above solution. React at 120°C for 6 hours and then at 200°C for 8 hours. After the reactor has completely cooled, rinse the sample repeatedly with ethanol and deionized water and dry it at 60°C for 6 hours.
[0020] Figure 1 The X-ray diffraction patterns of 1T MoS2 / Ni3S2 and 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalysts are shown in Figure 1. The diffraction peaks at 45 and 52.4° in the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst originate from NF (PDF#3-1051), the diffraction peak at 31° originates from the (110) plane of Ni3S2 (PDF#44-1418), and the diffraction peak at 31.88° originates from the (101) plane of 1T MoS2.
[0021] like Figure 2 As shown in Figure 2, scanning electron microscopy and elemental mapping analysis were performed on the 1T MoS2 / Ni3S2 nanocomposite electrocatalyst. 1T MoS2 was dispersed on the Ni3S2 nanosheets, and Mo, S, and Ni elements were evenly distributed on the sample surface.
[0022] like Figure 3 As shown in the figure, the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst was characterized by scanning electron microscopy, EDS spectroscopy, and elemental mapping. After sulfurization, a typical core-shell structure was formed, with the CNTs core and the 1TMoS2 outer layer. NF served as a Ni source, and after sulfurization, Ni3S2 was generated, forming a heterojunction with the 1T MoS2@CNTs core-shell structure on the surface. EDS analysis confirmed that the main components of the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst are C (60.43%), S (15.93%), Ni (20.45%), and Mo (3.2%). Elemental mapping also shows that Mo, Ni, C, and S are evenly distributed across the entire sample surface.
[0023] Figure 4Transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM) of 1T MoS2@CNTs / Ni3S2. 1TMoS2@CNTs consists of two parts: an inner CNT with a diameter of approximately 75 nm and an outer 1T MoS2 layer with a thickness of approximately 30 nm, demonstrating its core-shell structure. In the HRTEM image, the lattice spacing of 0.341 nm belongs to the (002) crystal plane of CNTs, the lattice spacing of 0.27 nm belongs to the (101) crystal plane of 1T MoS2, and the lattice spacing of 0.18 nm belongs to the (113) crystal plane of Ni3S2.
[0024] Figure 5 The electrocatalytic hydrogen evolution reaction properties of 1T MoS2@CNTs / Ni3S2 can be seen from the figure. -2 When 1T MoS2@CNTs / Ni3S2 is used, the overpotential is 227 mV and the Tafel slope is only 40.4 mVdec. -1 The charge transfer resistance is only 1.85 Ω, and the calculated Faradaic efficiency of 1T MoS2@CNTs / Ni3S2 is 96%. During long-term stability measurements, the response current density is well maintained, and after 1000 cycles, the overpotential does not increase significantly.
[0025] Figure 6 The electrocatalytic oxygen evolution reaction properties of 1T MoS2@CNTs / Ni3S2 can be seen from the figure. -2 When 1T MoS2@CNTs / Ni3S2 is used, it has a lower overpotential of 320 mV and a Tafel slope of 43.8 mVdec. -1 The charge transfer resistance is only 1.33 Ω, and the current density remains stable after 48 hours of continuous testing. After 1000 cycles, the overpotential does not increase significantly.
[0026] Figure 7 The full water splitting performance of the dual-electrode electrolyzer assembled with 1T MoS2@CNTs / Ni3S2 is shown. The 1T MoS2@CNTs / Ni3S2(+)||1T MoS2@CNTs / Ni3S2(-) electrolyzer only needs a potential of 1.39 V to reach 10 mA cm −2 The current density is less than that of Pt / C(-)||RuO2(+). The catalytic activity remains stable after a 48-h durability test, and the LSV curve after 1000 CV cycles also confirms its good stability.
Claims
1. A 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst, characterized in that: The 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst is an in-situ grown transition layer of vertically arranged large inner diameter thin-walled carbon nanotubes on nickel foam. A typical core-shell structure is formed with carbon nanotubes as cores and 1T MoS2 as shells on top of the carbon nanotubes. The nickel foam is used as a Ni source and generates Ni3S2 after sulfurization. It forms a heterojunction with the 1T MoS2@CNTs core-shell structure on the surface, forming a three-dimensional ordered array of 1T MoS2@CNTs / Ni3S2.
2. The method for preparing the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst according to claim 1, comprising the following steps: (1) In situ growth of CNTs on nickel foam: Dissolve 6.0-6.5 mmol of citric acid monohydrate (C6H8O7·H2O) in 14-16 mL of a 1:1 volume ratio of anhydrous ethanol and deionized water. After stirring for 10 min, add 0.4-0.5 g of urea and 0.1-1.0 mmol of large inner diameter, thin-walled carbon nanotubes. After sonication for 30 min, transfer the solution to a reactor (filling the reactor with no more than 80% of its capacity). Add nickel foam and react at 170-185°C for 12-18 h. After cooling the reactor, rinse the sample with ethanol and deionized water and dry it to obtain NF with CNTs grown on it. (2) Preparation of CNTs-supported 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst: Then, 1.5 mmol of thioacetamide and 0.5 mmol of sodium molybdate dihydrate were dissolved in 14-16 mL of a mixed solution of anhydrous ethanol and deionized water in a volume ratio of 1:1 and stirred evenly. The NF with grown CNTs was placed in a reactor. The solution filling amount should not exceed 80% of the reactor capacity. The above solution was added and reacted at 115-125 °C for 6 h-12 h, and then at 190-210 °C for 8 h-14 h. After the reactor was cooled, the obtained sample was washed and dried to obtain the CNTs-loaded 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst.
3. The method for preparing the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst according to claim 2, characterized in that: The nickel foam in step (1) is pretreated by the following steps: The samples were washed with 3.0 M HCl for 10 min, then washed with acetone and deionized water several times to remove surface impurities, and dried in a vacuum at 60 °C for 6 h.
4. The method for preparing the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst according to claim 2, characterized in that: The mixed solution in step (1) and step (2) is prepared by mixing 7.5 mL of anhydrous ethanol and 7.5 mL of deionized water.
5. The method for preparing the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst according to claim 2, characterized in that: In step (1), the reaction vessel was kept at 180°C for 12 h.
6. The method for preparing the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst according to claim 2, characterized in that: In step (2), the reactor was first reacted at 120°C for 6 h and then at 200°C for 8 h.
7. The method for preparing the 1T MoS2@CNTs / Ni3S2 nanocomposite electrocatalyst according to claim 2, characterized in that: In step (1), 0.7 mmol of large inner diameter thin-walled carbon nanotubes was added.